Class dynamics of development: a methodological note. Issue 10 (2nd October 2016) - Campling, Liam; Miyamura, Satoshi; Pattenden, Jonathan; Selwyn, Benjamin
Abstract: This article argues that class relations are constitutive of development processes and central to understanding inequality within and between countries. Class is conceived as arising out of exploitative social relations of production, but is formulated through and expressed by multiple determinations. The article illustrates and explains the diversity of forms of class relations, and the ways in which they interplay with other social relations of dominance and subordination, such as gender and ethnicity. This is part of a wider project to revitalise class analysis in the study of development problems and experiences.